Analysis of the Content and Efficacy of Limo Rhizome: A Herbal Blend That Is Beneficial for Health - Septia, Anggie Anggraini; Rhani, Nisrokah Aisyah; Ridho, Irvan Nur (CV. BImbingan Belajar Assyfa, 2024)
Limo rhizome, or limo rhizome, has long been known in traditional health practices for its significant health benefits. This study was conducted in Yogyakarta involving 50 consumers of limo rhizome. The main objective of this study was to analyze the content and benefits of this herbal drink, as well as to identify its contribution to overall health. The research method used was descriptive qualitative, with data collection techniques through structured interviews and direct observation in the field. The research instruments included an assessment of the health effects felt by consumers, such as improved digestion, regulation of the menstrual cycle, and increased body immunity. The results of the study showed that limo rhizome contains active compounds such as antioxidants and anti-inflammatories that play an important role in health. Of the 50 respondents, 85% reported improved digestive health, 78% experienced more regular menstrual cycles, and 90% felt healthier overall. The data analysis technique was carried out using a thematic analysis approach to identify the main themes from the data collected. This study concluded that limo rhizome drink, made from high-quality natural ingredients such as dried herbs, is not only safe but also effective in improving health. In addition to health benefits, the production and consumption of this drink also supports the creativity and economy of the local community.